2019
DOI: 10.33751/jhss.v3i2.1458
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Experience of E-Learning, Learning Process and Perceived Learning Outcomes in Economic Math Course

Abstract: This paper reveals research findings about the effect of E-learning experiences on student learning outcomes felt for Mathematics Economics courses. This study examines perceived learning outcomes in terms of effectiveness, number and productivity of learning in the context of E-learning. The participants were undergraduate students at the School of Economis EKUITAS. The results are interpreted using quantitative and verification research approaches. The results show that the E-learning experience of students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
1
9
0
1
Order By: Relevance
“…The framework and suggested recommendations promote a holistic approach when developing a website to accurately portray a school's identity and effectively address stakeholders' needs (Taddeo & Barnes, 2016). There is a significant significance between e-learning experiences in the Learning Process, which means an increase in the quality of learning that can be done by improving the learning process that first increased because the learning experience has no direct effect (Azis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The framework and suggested recommendations promote a holistic approach when developing a website to accurately portray a school's identity and effectively address stakeholders' needs (Taddeo & Barnes, 2016). There is a significant significance between e-learning experiences in the Learning Process, which means an increase in the quality of learning that can be done by improving the learning process that first increased because the learning experience has no direct effect (Azis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although participants have different programs, all participants have the same general subject, Statistics. Also, an important requirement that needs to be applied in e-learning research is that all participants involved in this activity are certain to have passed the Computer Introduction course [37]…”
Section: Figurementioning
confidence: 99%
“…Smith et al (2019) concluded that most of the learners' preferred online learning mode to other types provides more flexibility in learning, time management and offers more courses worldwide. Azis et al (2019) established that learners' experience on e-learning significantly influences the learning process's effectiveness and achieves indirect learning outcomes through the learning process.…”
Section: Introductionmentioning
confidence: 99%